The Sources on the History of Intellectual Heritage in Uzbekistan - Ziyayeva Dono Khamidovna (Universitas Muhammadiyah Sidoarjo, 2018)
The research analyses the sources relating to intellectual heritage of Uzbekistan in XIX – early XX centuries. There has been given the classification and types of sources, their significance to disclose history of Uzbekistan. There have been involved sources in five categories that were written in eight languages and main libraries, manuscript and archive funds where the sources are stored.